Pengaruh Sistem ERP Terhadap Pengelolaan Persediaan Bahan Baku Dengan Pengendalian Internal Sebagai Variabel Moderasi - Supriyadi, Agung; Firmansyah, Amrie; Surbakti, Lidya Primta (Universitas Teuku Umar, 2025)
In the era of digitalised business, Enterprise Resource Planning (ERP) has become an important tool for supporting operational efficiency. This study aims to analyse the effect of ERP on inventory management with internal control as a moderating variable. Data was collected from 30 respondents in the Procurement & Logistics and Sales & Marketing divisions, then analysed using the Structural Equation Modelling–Partial Least Squares (SEM-PLS) method. The results show that ERP has a positive effect on inventory management, and internal control significantly strengthens this relationship. The R-square value of 0.596 confirms that the model has adequate explanatory power. These findings have practical implications for decision makers, namely the importance of viewing ERP implementation not only as a technology project, but also as part of an organisational governance strategy. Strengthening internal control through standard procedures, monitoring mechanisms, and audit policies is key to ensuring the effectiveness of ERP and preventing inefficiencies in inventory management.